Assistance in Implementing the Strategy of the Surabaya City Industry and Manpower Service in Developing Small and Medium Industry Players: Pendampingan Implementasi Strategi Dinas Perindustrian Dan Tenaga Kerja Kota Surabaya Dalam Mengembangkan Pelaku Industri Kecil Menengah - Eriko Gravia Arlichandra; Nurkolish Majid (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
One of the main pillars of the national economy is small and medium industry (IKM). Today's trade dynamics require business actors, especially small and medium business actors, to increase the quality and volume of production in order to maintain the survival of the companies they supervise. The solution to this problem can be done through assistance to small and medium industries. The mentoring program launched by the Surabaya City Industry Service aims to improve the quality of IKM products. In this case, an IKM companion is needed. This activity was carried out within the framework of the MSIB (Certified Independent Study and Internship) Management Study Program, FEB UPN Veteran East Java, to support the Department of Industry mentoring program. Activities are carried out using qualitative methods in the form of socialization and observation. The results obtained are submitted to be implemented by the assisted IKM. It is hoped that these results can be used to develop their business in running their business.